Successful Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) deployment by emergency medicine physicians for refractory non-traumatic cardiac arrest - Graham Brant-Zawadzki; Guillaume L. Hoareau; H. Hill Stoecklein; Nicholas Levin; Craig H. Selzman; Anna Ciullo; Joseph Tonna; Christopher Kelly; Jamal Jones; Scott T. Youngquist; M. Austin Johnson (Resuscitation Plus, 2024)
Aim: Cardiac arrest afflicts over 600,000 people annually in the United States. Rates of survival from cardiac arrest have remained stagnant for decades. Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) is most commonly used in the management of severe hemorrhagic shock, primarily for non-compressible thoracoabdominal trauma. A growing body of evidence suggests it may serve a role in augmenting cardiac and cerebral perfusion in non-traumatic, refractory cardiac arrest. Typically, REBOA is deployed by interventional radiologists under real-time fluoroscopy. Limited data exist to demonstrate the feasibility or logistics of successful REBOA deployment in emergency departments by emergency medicine physicians. Methods: We describe an emergency medicine-driven training program and treatment protocol developed to deploy REBOA in the emergency department for patients experiencing refractory out-of-hospital cardiac arrest and deemed ineligible for ECPR. We detail the training, certification processes, and clinical outcomes from our first eight cases. Results: Five emergency medicine physicians underwent training for REBOA placement through a didactic curriculum and hands-on training with mannequin and live tissue porcine models. Since protocol implementation, eight patients have undergone REBOA catheterization by emergency medicine physicians: 5 males and 3 females, age range 25–79. The first pass success was 8/8 (100 %), and all 3 commercially available catheters in the United States were successfully used. ROSC was achieved in 3/8 (37.5 %) patients, although no patients survived to hospital discharge. No REBOA catheter-associated complications were identified. Conclusions: This series demonstrates feasibility of emergency physician placed REBOA for non-traumatic, refractory cardiac arrest a novel resuscitative technique. Through a combination of focused education, innovative technology use, robust large animal model-based training, and strategic procedural integration, we showcase the potential for emergency departments to spearhead the adoption of this potentially life-saving intervention.